Mucinous biliary obstruction associated with a cholangiocarcinoma - Necmettin KARAEREN; Can UYGURER; Ergün SARAÇOĞLU; Celalettin ÇETİN; Sait BAĞCI; Mustafa GÜLŞEN; Ahmet UYGUN; Kemal DAĞALP; Burhan ŞAHİN; Ahmet ALPER (Turkish Journal of Gastroenterology, 2019)
-